A critical analysis on enhancing procurement process in public sector technical and university education in Bangladesh - Ali MCIPS, S. M. Wazed (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.